Kisceral Argumentation in Law: Past and Present, Here and There - Novak, Marko (Informal Logic, 2022)
Gilbert's kisceral argumentation is, roughly speaking, about arguing based on intuitions. In the forefront of such a (rhetorical) model are arguers and audiences, who resolve disagreements using kisceral arguments. Intuitions as reasons were more important in pre-modern law, when the law was not as explicit, precise, and determinate as today. Law influenced by religion or religious law was a typical example. In our much more secular modern era, intuitions are more or less subordinated to the (legal) logical mode of arguing. However, in tough legal cases, when logic "runs out," it is values that decide them. Not surprisingly, neuroscience and cognitive psychology have shown a strong connection between values and intuition.